Heat transfer of aqueous suspensions of carbon nanotubes (CNT nanofluids) - Ding, Yulong; Alias, Hajar; Wen, Dongsheng; Williams, Richard A. (Elsevier BV, 2000)
This paper is mainly concerned about the heat transfer behaviour of aqueous suspensions of multi-walled carbon nanotubes (CNT nanofluids) flowing through a horizontal tube. Significant enhancement of the convective heat transfer is observed and the enhancement depends on the flow conditions (Reynolds number, Re), CNT concentration and the pH, with the effect of pH smallest. Given other conditions, the enhancement is a function of axial distance from the inlet, increasing first, reaching a maximum, and then decreasing with increasing axial distance. The axial position of the maximum enhancement increases with CNT concentration and Re. Given CNT concentration and the pH level, there appears to be a Re above which a big increase in the convective heat transfer coefficient occurs. Such a big increase seems to correspond to the shear thinning behaviour. For nanofluids containing 0.5 wt.% CNTs, the maximum enhancement reaches over 350% at Re = 800, which could not be attributed purely to the enhanced thermal conduction. Particle re-arrangement, shear induced thermal conduction enhancement, reduction of thermal boundary due to the presence of nanoparticles, as well as the very high aspect ratio of CNTs are proposed to be possible mechanisms.